2014
DOI: 10.1371/journal.pone.0109427
|View full text |Cite
|
Sign up to set email alerts
|

PSMA-Specific CAR-Engineered T Cells Eradicate Disseminated Prostate Cancer in Preclinical Models

Abstract: Immunology-based interventions have been proposed as a promising curative chance to effectively attack postoperative minimal residual disease and distant metastatic localizations of prostate tumors. We developed a chimeric antigen receptor (CAR) construct targeting the human prostate-specific membrane antigen (hPSMA), based on a novel and high affinity specific mAb. As a transfer method, we employed last-generation lentiviral vectors (LV) carrying a synthetic bidirectional promoter capable of robust and coordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 44 publications
4
64
0
Order By: Relevance
“…Several prostate tumor models, both human and murine origins, have been described and used to study the targeting of hPSMA-CAR T cells, but some limitations have been identified 21, 24, 48, 49. We focused on murine cell lines, with prospective to utilize them in a syngeneic mouse model using immunocompetent mice.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several prostate tumor models, both human and murine origins, have been described and used to study the targeting of hPSMA-CAR T cells, but some limitations have been identified 21, 24, 48, 49. We focused on murine cell lines, with prospective to utilize them in a syngeneic mouse model using immunocompetent mice.…”
Section: Resultsmentioning
confidence: 99%
“…Oncol., abstract). It has been shown that adoptive transfer of T cells modified with the anti-hPSMA CAR could specifically mediate regression of pulmonary experimental lung metastasis in SCID mice 21, 24, 49. However, this approach was ineffective against established subcutaneous tumors, 49 unless the CAR T cells were injected locally 49 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The TM domain is usually derived from CD3ζ [74], CD4 [75,76], CD8 [47,60,68], or CD28 [70,75,77] molecules and is inserted between the hinge region and the signaling endodomains. It has significant effects on the cell surface expression of CARs.…”
Section: Car Hinge and Transmembranementioning
confidence: 99%